Modelling damping element to reduce disc brake squeal - Md. Yusop, Noraide (2013)
A disc or drum brake system is very often generating undesirable and annoying squeal noise that can disturb both driver and passengers. In order to prevent or reduce brake squeal noise, structural modifications of brake components, damping layers and active squeal control methods are commonly proposed and evaluated by car manufacturers using analytical, numerical and experimental approach. Thus, this thesis attempts to investigate the effectiveness of damping layers such as pad insulator and clip to reduce disc brake squeal noise. In doing so, existing two (pad model) and four (pad-disc model) degrees-of-freedom (DOF) brake models without damping layers are adopted. The mass, stiffness and damping values of these brake models are obtained from the experiments. These two brake models are then validated against a real brake assembly test data and good correlation on the natural and squeal frequency is achieved. Upon obtaining validated brake models, damping layers i.e. the clip and insulator are modelled based on its mass, stiffness and damping. The layers later are embedded into the validated pad and pad-disc models. The parameter properties (stiffness and damping) of these damping layers are measured from modal testing. Complex eigenvalue (CE) and dynamic transient (DT) analyses are performed using MATLAB software package to predict squeal occurrences. The squeal trigger mechanism used in this work is based on mode coupling effect. The brake models with damping layers are simulated at a certain brake parameter range such as friction coefficient, pad-disc contact stiffness and pad wear. From the analysis, it is found that both CE and DT predict squeal frequency close to the measured data with difference less than 4%. It is also found that the pad-disc model is successfully predicting squeal or non-squeal occurrences close to the squeal test results for both with clip and clip-insulator models. However, the pad model is seen not capable to completely replicate the squeal test results particularly with the clip model. This shows that the pad-disc model should be used to predict squeal occurrences. From the parametric studies, it is shown that squeal noise can be